1999
DOI: 10.1006/dbio.1998.9181
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ihh and BMP/Noggin Signaling during Cartilage Differentiation

Abstract: Bone morphogenetic proteins (BMPs) have been implicated in regulating multiple stages of bone development. Recently it has been shown that constitutive activation of the BMP receptor-IA blocks chondrocyte differentiation in a similar manner as misexpression of Indian hedgehog. In this paper we analyze the role of BMPs as possible mediators of Indian hedgehog signaling and use Noggin misexpression to gain insight into additional roles of BMPs during cartilage differentiation. We show by comparative analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
161
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 223 publications
(177 citation statements)
references
References 54 publications
10
161
0
2
Order By: Relevance
“…Early studies demonstrated that BMPs when introduced at intramuscular sites in adult mice induce ectopic endochondral bone development [Wozney et al, 1988]. Studies of the roles of this family of proteins in endochondral bone development have been complicated by the large number of BMP proteins that are differentially expressed and regulated in the developing skeleton [ Vortkamp et al, 1996;Pathi et al, 1999]. TGFb and BMPs bind to serine/threonine kinase receptors.…”
Section: Bone Morphogenic Proteins As Mediators Of Ihh Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies demonstrated that BMPs when introduced at intramuscular sites in adult mice induce ectopic endochondral bone development [Wozney et al, 1988]. Studies of the roles of this family of proteins in endochondral bone development have been complicated by the large number of BMP proteins that are differentially expressed and regulated in the developing skeleton [ Vortkamp et al, 1996;Pathi et al, 1999]. TGFb and BMPs bind to serine/threonine kinase receptors.…”
Section: Bone Morphogenic Proteins As Mediators Of Ihh Regulationmentioning
confidence: 99%
“…Within the developing limbs, BMP2, 4, and 7 are expressed in the perichondrium, while BMP6 is found in pre-hypertrophic and hypertrophic chondrocytes [Vortkamp et al, 1996;Pathi et al, 1999]. Zou et al [1997] first reported that overexpressing a constitutively active mutant of BMP type IA receptor induced PTHrP expression in the periarticular perichondrium.…”
Section: Bone Morphogenic Proteins As Mediators Of Ihh Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ihh/ PTHrP negative feedback loop acts to put the brakes on at the junction between the end of proliferation and the initiation of hypertrophy, requiring communication between growth plate chondrocytes and the perichondrium (Vortkamp et al, 1996;Long and Linsenmayer, 1998;Pathi et al, 1999;Volk and Leboy, 1999;Pateder et al, 2000;DiNino et al, 2002;Allen et al, 2004). Recent studies provide data that vascular endothelial growth factor (VEGF) alters the permeability characteristics of the vascular endothelium in paracrine regulation of the growth plate involving the perichondrium (Roberts and Palade, 1995;Esser et al, 1998;Zelzer et al, 2002;Ericksson et al, 2003;Aramoto et al, 2004;Cao et al, 2004;Zelzer and Olsen, 2005).…”
Section: Mpm Imaging Allows Morphological Definition Of Subperichondrmentioning
confidence: 99%
“…Furthermore, the activity of Notch signaling is mediated by the glycosyltranferase Fringe (Aulehla and Johnson, 1999;Barrantes et al, 1999;Moloney et al, 2000;Zhang and Gridley, 1998), further demonstrating the fine tuning of Notch signaling activity by biochemical mechanisms. Mice with a disruption of the lunatic fringe gene display defects in somite formation as well as in anterior posterior patterning of the somites (Zhang and Gridley, 1998).…”
Section: A Intercellularmentioning
confidence: 96%